The Arbiters of Faith: Legislative Assembly of BC Entanglement with Religious Dogma Resulting from Legislative Prayer - Bushfield, Ian (Secularism and Nonreligion, 2020)
Daily sittings of the Legislative Assembly of British Columbia (BC), Canada begin with a prayer or reflection delivered by a Member of the Legislative Assembly (MLA). MLAs have the option of using a sample prayer from a list of five provided by Legislative staff, or of delivering a prayer of their own devising. The Office of the Clerk is currently revising the list of sample prayers to include a greater diversity of beliefs. To accomplish this task, bureaucrats face a number of practical and constitutional challenges. This article explores these challenges. The Office of the Clerk will have to first identify religious and belief groups that are present in BC, then select a reasonable number of those groups to include on the list, and finally identify prayers and reflections that are representative of those traditions. Each of these steps raises practical questions with respect to how bureaucrats can actually make these decisions, and to more fundamental questions regarding the appropriateness of the decisions made. Given these challenges, this paper concludes that the practice of offering sample prayers should be avoided, and that MLAs should be called upon to deliver prayers and reflections of their own devising, or that legislative prayer be abolished.